ANALYSIS OF SMOKING HABITS AND MONOXIDE CARBON CONTENTS IN HOME WITH CARBOXIHEMOGLOBINE (COHb) IN ACTIVE SMOKING IN III ENVIRONMENT, KEMARAYA, KENDARI CITY: ACTIVE SMOKING - Sari Arie Lestari B.; Titi Saparina L.; Leniarti Ali (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2021)
Background: around 10,000,000 people is estimated to be death per year by 2020 because of smoking. Smokers emit smoke  around 20,000 ppm of CO, when it is inhaled. It will become diluted with a concentration of around 400 until 5,000 ppm. This situation is dangerous because it will increase the COHb concentration in the human blood by up to 6.9%. It can  prone to heart attacks. The purpose of this research is to analyze smoking habits and CO levels in the house with carboxyhemoglobin (COHb) levels in active smokers in 3  Districts of Kemaraya in Kendari City. Methods: The research was conducted using the Analytical Descriptive method. Data were collected by interview using a structured questionnaire and laboratory analysis. While the approach used is a cross-sectional study. The population in this study was 81 and the number of samples was 45. Results: The  The results obtained were that there was no  relationship between CO and COHb levels ( p value = 0.623> 0.05); there was a weak relationship between smoking and COHb levels (p value= 0.029 <0.05); and there is a low relationship between the number of cigarettes and COHb levels ( p value= 0.0298 <  0.05). Conclusion: It can be concluded that there is an insignificant relationship between smoking duration, types of cigarettes smoked, number of cigarettes smoked and levels of carbon monoxide in the house and levels of carboxyhemoglobin (COHb) in active smokers in environment III District of Kemaraya Kendari City.